2014
DOI: 10.1021/cg401073n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes upon Dehydration of Amorphous Calcium Carbonate

Abstract: Amorphous calcium carbonate (ACC) is a common transient precursor to biogenic crystalline calcium carbonate, but factors controlling the amorphous to crystalline transformation remain unclear. We present a structural analysis and comparison of hydrated and partially dehydrated, synthetic ACC samples. Thermogravimetric analysis showed total H 2 O losses of 46% with heating to 115 °C and 75% for heating to 150 °C. The 1 H NMR spectra of hydrous ACC, obtained both directly and indirectly, via 13 C-detection, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
135
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(162 citation statements)
references
References 45 publications
24
135
0
1
Order By: Relevance
“…Recent thermal and structural studies have characterized these three steps in ACC dehydration as loss of fluidlike mobile → restrictedly mobile and rigid H 2 O components → final loss of hydroxyl and trapped rigid and mobile water. 44,46 Further, these studies suggested that the fluidlike mobile water behaves more like physically adsorbed water and is lost in early stages of dehydration, while restrictedly mobile and rigid H 2 O components are lost at intermediate temperatures. The loss of the final fraction of hydroxyl/trapped water above 300°C is found to be crucial as it triggers the crystallization.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent thermal and structural studies have characterized these three steps in ACC dehydration as loss of fluidlike mobile → restrictedly mobile and rigid H 2 O components → final loss of hydroxyl and trapped rigid and mobile water. 44,46 Further, these studies suggested that the fluidlike mobile water behaves more like physically adsorbed water and is lost in early stages of dehydration, while restrictedly mobile and rigid H 2 O components are lost at intermediate temperatures. The loss of the final fraction of hydroxyl/trapped water above 300°C is found to be crucial as it triggers the crystallization.…”
Section: Resultsmentioning
confidence: 94%
“…The loss of the final fraction of hydroxyl/trapped water above 300°C is found to be crucial as it triggers the crystallization. 44,46,49 Similarly, Ihli et al 44 have identified four stages in the mechanism of dehydration of ACC leading to crystallization as stage-I: loss of surface-bound water at ∼40°C, stage-II: loss of water from the interior of the ACC with shrinkage of ACC particles around 140°C, stage-III: expulsion of the most deeply located water around 290°C, and stage-IV: crystallization to calcite at 315°C. In this work, to avoid any structural changes upon heating or crystallization, the first set of water adsorption calorimetric experiments was carried out on amorphous samples degassed 6−8 h under vacuum at 25°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although our model ACC Ik shows the most segregation of water within the structure, it does not give the slowest diffusivity for the ions. While the more mobile water will be more likely to leave the system during dehydration, full dehydration is likely to require further structural changes 26 .…”
Section: Atom and Ion Mobilitymentioning
confidence: 99%
“…Proton solid-state nuclear magnetic resonance showed that two different types of water are present within the structure. One is largely immobile and labelled as structural, but the other showed an increased mobility 22,25,26 . The location of this water appears, again, to be dependent on the sample origin.…”
Section: Introductionmentioning
confidence: 99%